REDUCTION OF CONSTIPATING SCORING SYSTEM AMONG WOMEN AGED 18-25 YEARS OLD AS A RESULT OF DECOCTED TRENGGULI (CASSIA FISTULA L.) - Jannah, Isnaini Nur; Mustika, Arifa; Puruhito, Edith Frederika (Journal of Vocational Health Studies, 2017)
Background: Constipation is a condition when someone has difficulty to defecate. Constipation is indicated by hard and large size stool as well as a decrease frequency of bowel movement. Commonly, constipation is indicated by anxiety during bowel movement due to disruption defecation. Constipation can cause severe stress resulting from discomforts for patient. The severity of the constipation can be measured using the Constipation Scoring System (CSS). CSS is a scoring system for patient, which based on the answers about the symptoms being asked in the questionnaire. One of the herbs to handle the problem of constipation that have a laxative effect is Trengguli (Cassia fistula L.) originate from the family Fabaceae. The part that can be used for a laxative is a Trengguli fruit. A decocta method to Trengguli flesh of the fruit for a laxative, since decocta method generates the highest total anthraquinone glycosides for the use of laxatives. Purpose: The purpose of this study was to prove the effectiveness of decocta pulp of trengguli for the reduction of constipation scoring system among women aged 18- 25 years old with constipation problem. Method: The method used is quasi-experimental design using a design of one group pre-post test. The study was conducted in December at the clinic Battra Airlangga University School of Medicine with 26 responded. Data were analyzed using SPSS with the Wilcoxon test. Result: The results of this study showed that the decocta pulp of trengguli(Cassia fistula L.) has significant effectiveness with p = 0.000 with p <0.05 on a decrease in constipation scoring sytem for constipation treatment among women aged 18-25 years.